Early processing of traumatic material and contextual information in posttraumatic stress disorder and its relation to memory impairments - Zidda, Francesca; Steiger-White, Frauke; Winkelmann, Tobias; Ruttorf, Michaela; Andoh, Jamila; Nees, Frauke; Flor, Herta (Scientific reports, 2025)
Posttraumatic stress disorder (PTSD) is characterized by exaggerated responses to trauma-relevant cues and impairments in relation to contextual information. However, it is not clear whether this dysfunction is related only to memory processes, or whether early perceptual and attentional processing is already dysfunctional. We examined early processing and retrieval of trauma-related cues and neutral contexts in 20 individuals diagnosed with PTSD (PTSD) and 20 trauma-exposed controls without diagnosis of PTSD (NPTSD) using simultaneous high-density electroencephalography and eye-tracking. A group of 20 non-trauma-exposed healthy controls (HC) was employed to test for responses to trauma-unrelated cues and contexts. The earliest visual event-related potential (C1) was positive for individuals diagnosed with PTSD and negative for NPTSD, suggesting enhanced early visual processing of the cue. Eye-tracking showed that PTSD but not NPTSD displayed significantly longer latencies before looking at contexts than at trauma-related cues. The PTSD group performed significantly worse than the NPTSD group in correctly retrieving rearranged cue/context associations compared to consistent associations. Memory strength for rearranged cue-context pairs was significantly predicted by the early processing measures of the context. Perception of traumatic cues in neutral contexts is biased in PTSD at early processing stages and contributes significantly to the impairment in context-relational memories. For trauma-unrelated cues and contexts no significant differences emerged between PTSD and trauma-exposed as well as non-trauma-exposed controls. Treatments for individuals diagnosed with PTSD should focus on early processing, perception and attention of cue/context traumatic associations in addition to contextual memory.
Gesehen am 21.08.2025